(untitled) (Journal of Parents and Teachers, 2016)
Traditionally, family socialization has been conceptualized as an important correlate of psychological well-being and a basic theoretical construct for explaining adjusted and adaptive behaviors into society. The assessment of the socialization process requires of a theoretical perspective that conceptualizes how parents can influence their children. Based on the classic two-dimensional model of socialization, with the dimensions of acceptance/involvement and strictness/imposition, four parenting styles were defined: indulgent, authoritative, neglectful and authoritarian. The ESPA29 scale is suitable for evaluation of family socialization.